Comportamiento agronómico del cultivo de pepino (Cucumis sativus l.) con diferentes abonos orgánicos en la finca experimental La María UTEQ, año 2014 - Bustamante Mera, Elia Zobeida (2015)
In the present research work seeks alternatives for the production of cucumber (Cucumis sativus L), establishing the maximization of production considering the amount and quality of the product using organic fertilizers such as Jacinto de agua and humus, establishing general objective "Evaluate the agronomic performance of the cucumber (Cucumis sativus L.) with different organic fertilizers, at the Experimental Center La María, year 2014 " Using the design of randomized complete block (BDCA), 7 different treatment were applied T1: 1 kg of humus / m2, T2: 3 kg of humus / m2, T3: 5 kg of humus / m2, T4: 1 kg of Jacinto de Agua / m2 , T5: 3 Kg of Jacinto de Agua / m2, T6: 5 kg of Jacinto de Agua / m2 and T7 Witness, with 4 repetitions each, considering the following variables: plant height and stem diameter field every 15 days, weight and diameter of the fruit and yield per m2, using the Tukey test ranges with 95% probability of error. For the experiment was a total area of 208.10 m2, divided into plots of 7.20 m2, with a population of 20 plants per experimental unit and evaluation of 6 plants. The economic analysis involved each of the generated costs for the production of cucumber (Cucumis sativus L.) considering the different treatments, covering the cost of inputs, labor, rent and depreciation. The price of the product on the market was $ 1.12 per kg. After the investigation it was determined that the highest level of production was achieved with treatment T6: 5 kg of Jacinto de agua / m2 also obtaining higher profits and cost-benefit ratio of 1.53, demonstrating the validity of the hypothesis that says "Jacinto de agua fertilizer will give the best production dosage 5 kg / m2".